IMPACT OF SERVICE QUALITY ON CUSTOMERS’ RETENTION IN COMMERCIAL BANKS AT VIRUDHUNAGAR DISTRICT - Dr. M.Vairavan,; Golden, S. Anthony Rahul (International Journal of Psychosocial Rehabilitation, 2020)
The customer retention is a very interesting and important topic in the service industry especially in banking sector. Service quality is usually understood as a measure of how well the level of the delivered services matches the customer’s expectations (Santos, 2003). Most of the Indian Banks perform the same functions. Therefore, customers place service quality on the top in their priority list while choosing a particular bank. Banks prosper or decline majorly depends on the quality of service offered to the customers. Due to dependence on quality service majority of the banks in India have placed service quality at the top of the list of business strategy. In this study, the researchers have chosen sample respondents from six public banks and four private banks working in the Virudhunagar District, Tamilnadu, India. It is descriptive because descriptive data were collected through detailed customer survey and interviews. It is also explanatory since it tried to explain the relationship between the service quality in banking and customer retention, also realized that for better understanding of the relationship between service quality and customer retention. 120 Sample Respondents were selected for the study using simple random sampling. In this study, Service quality is commonly noted as a critical prerequisite for establishing and sustaining relationship with valued customers. Several studies have shown that a high level of customer service quality can exert a positive influence on customer satisfaction and retention. In this study, it is found that a positive and moderately significant relationship exists between Customer Retention and Service Quality.